Emotional dependency and its relationship with domestic violenceA descriptive approach to literature review - Hilario Ramos, Gina Eloisa (2020)
Emotional dependency is considered as a need for affection from an external person to feel valued, sometimes becoming a maladaptive pattern. On the other hand, it is also linked to violence during a relationship. Objective. To review descriptive literature on emotional dependence with physical violence, psychological and sexual violence, and the psychodynamics of couples through a descriptive literature review. Method. It was a qualitative study of descriptive review of the literature. A search was made in three electronic databases, ScienceDirect, SciELO, Directory of Open Access Journals, and a total of 15 original scientific articles were worked on. Results. Literature indicates that there is significance among people who are emotionally dependent on their partner with the presence of physical violence, psychological or sexual violence within a relationship. Therefore, the affected person takes it as normal, minimizing the abuse suffered and justifying itself as part of a "normal" behavior of the couple. The authors also concluded that, within a relationship, emotional dependence has a higher incidence with psychological violence with verbal abuse that was not considered as an offense and, on many occasions, this type of violence is not considered as such. Conclusion. Studies agree that there is a significant relationship between emotional dependence and violence. Likewise, it is appreciated that emotional dependence is more prevalent in women than in men, and among the types of violence, psychological violence is one of the most practiced.